Bermuda Triangle - Donkin, Andrew (Dorling Kindersley readers. Reading alone., 2000)
Explores the mysteries and legends associated with the Bermuda Triangle, an area in the Atlantic Ocean bounded by Bermuda, Florida, and Puerto Rico, where hundreds of boats and planes have vanished.